High Tunability in (111)‐Oriented Relaxor Pb0.8Ba0.2ZrO3 Thin Film with Antiferroelectric and Ferroelectric Two‐Phase Coexistence. Issue 6 (22nd March 2013) - Peng, Biaolin; Fan, Huiqing; Zhang, Qi; Feteira, A.
<x xml:space="preserve">Abstract</x> Using a sol‐gel method Pb0.8Ba0.2ZrO3 (PBZ) thin film with a thickness of 320 nm was fabricated on Pt(111)/TiOx/SiO2/Si substrate. The analysis results of XRD, SEM, and dielectric properties revealed that this thin film is a (111)‐oriented nano‐scaled antiferroelectric and ferroelectric two‐phase coexisted relaxor. Calculations of dielectric tunability (η) and figure‐of‐merit (FOM) at room temperature display a maximum value of 75% at E = 560 kV/cm and 236, respectively. High‐temperature stability (η > 75% and FOM > 230 at 560 kV/cm in the range from 300 to 380 K) and high breakdown dielectric strength (leakage current < 1 nA at 598 kV/cm) make the PBZ thin film to be an attractive material for applications of tunable devices.